Early interventions for the prevention of post-traumatic stress symptoms in survivors of critical illness: protocol for a systematic review. Issue 9 (1st September 2017) - Glaspey, Lindsey J; Roberts, Michael B; Mazzarelli, Anthony; Trzeciak, Stephen; Roberts, Brian W
Abstract : Introduction: Post-traumatic stress disorder (PTSD) is being increasingly reported among survivors of critical illness and injury. Previous work has demonstrated that PTSD reduces patient quality of life and ability to return to work, as well as increases healthcare costs. As such, identifying interventions aimed at preventing the development of critical illness-related PTSD could have an important public health impact. The objective of this systematic review is to collate the world's literature on early interventions aimed at preventing PTSD among survivors of critical illness. Methods and analysis: We will perform a qualitative systematic review of human clinical trials of interventions aimed at preventing or reducing critical illness-related PTSD symptoms. We will methodically search CENTRAL, MEDLINE, Embase and CINAHL. We will also search websites containing details on clinical trials registration (National Library of Medicine's ClinicalTrials.gov and the WHO's International Clinical Trials Registry Platform), as well as screen reference lists of the articles we select for inclusion to identify additional studies for potential inclusion. Two authors will independently review all search results. After identification and inclusion of articles, we will use a standardised form for data extraction. We will use tables to describe the study type, populations, interventions tested and timing of interventions, outcome measures and effects of interventions on outcome measures compared with control groups. This review will be completed between 1 August 2017 and 31 August 2017. Ethics and dissemination: The proposed systematic review will not collect individual patient level data and does not require ethical approval. Results of this study will contribute to the understanding of critical illness-related PTSD and help prompt future research aimed at further developing interventions to prevent PTSD symptoms in survivors of critical illness. PROSPERO registration number: This systematic review is registered in the PROSPERO international prospective register of systematic reviews (registration number CRD42017069672).